Evaluation of Pregnancy Outcome and Influencing Factors of Microsurgical Tubal Recanalisation as a Reversal of Tubal Ligation in a Tertiary Hospital - Naskar, Animesh; Gharami, Somasree; Mandal, Aparna Khan; Mandi, Bharat Chandra; Das, Rupkamal (Asian Journal of Medical Sciences, 2022)
Background: Tubal microsurgical recanalization is a procedure which restores the fertility in women who have undergone sterilization voluntarily, thinking that her family is complete. However due to unforeseen circumstances, 1–3% of these women subsequently demand reversal of sterilization. Aims and Objectives: This study aims to evaluate the pregnancy rate after reversal surgery and to find out the various factors that influence the success of tubal microsurgical recanalization. Materials and Methods: The current study was hospital-based retrospective one involving 48 women undergoing reversal of sterilization at the department of gynecology and obstetrics in tertiary hospital, Kolkata, during the period of 3 years, from July 2015 to June 2018. The women were followed up for a period of 1 year by telephonic contact. Women seeking tubal recanalization was in age group of 20–35 years with normal ovulation and normal semen analysis. Women, >35 years old, anovulation, with obvious pelvic inflammatory disease, endometriosis or fibroid were excluded, women with any contraindications to pregnancy or surgery and any male factor infertility also excluded from the study. Results: Out of 48 study subjects, intrauterine pregnancy was achieved in 27 cases (93.1%)), 2 patients (6.9%) had ectopic pregnancy. Out of 27 intrauterine pregnancies, 4 had abortions (13.8%), 3 (10.3%) are ongoing pregnancies, and 20 patients had live birth (69%). Conclusion: Tubal microsurgery offers good chances of pregnancy outcome which is favored by the age below 30 years, interval between sterilization and its reversal <4 years, isthmo-isthmic anastomosis, reconstructed tubal length being more than 6 cm, and type of previous sterilization were by Pomeroy’s method.